Effects of the Usage of Social Media on Political Socialization of Youth: Adolescents, Political behavior, Political socialization, Social media - khan, Samiullah; Asim Razzaq; Asif, Sadaf; Ahmad, Raza Waqas (Journal of Peace, Development and Communication, 2020)
This research is conducted to explore how much social media involved in engaging Pakistani adolescents towards political socialization. In addition, how they are participating and what impact of their participation is reflecting on their political motivation, political behavior, and voting tendency. It was a tentative estimate that social media plays a significant role in political socialization. To explore this prospect, Uses and Gratification school of thought were closer to this research, which questions about what are the purposes behind the use of social media and what urges youth to use them? This theory also suggests that the usage of these social mediums varies from user to user where everyone has the right to use these for their satisfaction. This study is grounded on quantitative analysis in which the survey method is used with a Non-probability sampling technique and respondents have been selected through convenient sampling to obtain a representative sample by using sound judgment. The study explored the usage of media by gender and purpose. Moreover, the relation between social media and political socialization is also observed in this study. For this purpose, statistical tests are also applied to gathered data. It can be concluded that the usage of digital media in Pakistan politicizes the youth and that affects the voting behavior of its users. As Pakistan is not considered suitable for demonstrations due to internal threats that’s why individuals could not participate physically. Therefore, most of the users share their views online because it is convenient and safest platform for them to reveal their concerns.